Konstruksi Hukum Perdata terhadap Perlindungan Data Pribadi dalam Transaksi Komersial Analisis Perspektif Hak Keperdataan Digital - Shodiq, Rahmat; Maharani, Yolanda Indah; Christian, Kelvin Daniel; Rahwati, Sri (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
The rapid growth of digital transactions in Indonesia has not been accompanied by a sufficient legal framework to protect personal data as an economic asset. This study aims to construct a private law framework that recognizes personal data as an object of proprietary rights within commercial transactions. Employing a normative juridical method with conceptual and comparative approaches, the research analyzes national regulations, particularly Law No. 27 of 2022 on Personal Data Protection. It contrasts them with international standards such as the General Data Protection Regulation (GDPR). The findings reveal that Indonesia’s regulatory focus remains predominantly administrative, lacking recognition of personal data as an independent property right. Through a systematic conceptualization of personal data as a digital object possessing economic value, this study proposes a new model for personal data protection grounded in property law principles. The proposed framework offers more substantial legal certainty for individuals. It addresses the power imbalance between data subjects and digital business actors, contributing significantly to the development of more equitable and adaptive regulations in the digital economy.